Molecular docking and molecular dynamic simulations of inhibitor ZJ0777 and CIE binding to acetohydroxyacid synthases - Wang, Maojun; Xuan, Nanxia; Wu, Jun (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2015)
Acetohydroxyacid synthases(AHAS) which play an important role in biosynthesis of branched chain amino acid, are a group of enzymes widely distributed in plants and microorganism, and it is a popular target of many herbicides. ZJ0777 is a novel herbicide possessing many merits including low toxicity, low residue and high selectivity. The interaction between ZJ0777 and AHAS is studied via molecular docking using discovery studio program. The docking results indicate that ZJ0777 mainly interacts with residue Arg377, Trp574 and Ser653, which is very similar to the binding model of CIE in the crystal structure of AHAS-CIE complex. CIE has more hydrogen bond interactions with AHAS, and ZJ0777 has more pi - pi interactions with AHAS. AHAS-ZJ0777 complex obtained by docking and AHAS-CIE complex are performed 1135 ps molecular dynamics (MD) simulations. Root-Mean-Square deviation (RMSD) of the backbone atoms and the inhibitor atoms with respect to starting structure are calculated to estimate the quality and convergen